STRATEGI OPTIMALISASI KAPABILITAS EKONOMI KREATIF BERBASIS GENDER EQUALITY AND SOCIAL INCLUSION DALAM UPAYA IMPLEMENTASI TECHNOPRENEURSHIP TOURISM DI DAERAH PERBATASAN - Vuspitasari, Benedhikta Kikky; Usman, Usman; Atlantika, Yeremia Niaga; Sumarni, Margaretha Lidya (JURNAL LENTERA BISNIS, 2026)
This research focuses on strategies to optimize the capabilities of the creative economy based on Gender Equality and Social Inclusion (GESI) in the implementation of technopreneurship tourism in the border region of Bengkayang Regency, West Kalimantan. The study is motivated by the substantial potential of natural resources, cultural assets, and the strategic location of the border area, which remain underutilized, particularly by women and marginalized groups. Digitalization is considered a promising approach to enhance business efficiency, expand market access, and foster sustainable tourism models. However, limited digital skills, inadequate infrastructure, and gender disparities present significant challenges. A descriptive qualitative method was employed through observations, in-depth interviews, focus group discussions (FGDs), and secondary document analysis. Data were analyzed thematically, focusing on local potential, gender dynamics, market access, technological capacity, and social inclusion. The findings reveal that the main creative economy potentials include tengkawang-based processing, traditional weaving and handicrafts, culinary heritage, and cultural tourism. Women are dominant in traditional sectors but remain underrepresented in digital-based activities. Key obstacles include limited capital, low levels of digital literacy, narrow market access, and prevailing social norms restricting women’s roles. Marginalized groups also face discrimination and limited access to basic services. The proposed strategies emphasize gender-responsive technical capacity building, inclusive digital literacy, strengthening of creative economy institutions, and cross-sectoral policy integration sensitive to GESI principles. The study recommends pentahelix synergy as a crucial approach to strengthening an inclusive and sustainable creative economy ecosystem in border areas through the application of digital-based technopreneurship tourism.